(untitled) (Eurasian Research Bulletin, 2026)
This study explores the development of a modern management model for sports activities in higher education institutions in the context of contemporary educational reforms and global trends in sports management. The increasing importance of student health, physical activity, and institutional competitiveness has necessitated the modernization of sports management systems within universities. The research analyzes theoretical foundations of sports management, identifies key organizational, pedagogical, and technological factors influencing the effectiveness of sports activities, and proposes a comprehensive management model integrating digital technologies, strategic planning, and competency-based approaches. The findings indicate that the implementation of an innovative sports management model significantly improves student participation, enhances organizational efficiency, and contributes to the development of sustainable sports ecosystems in higher education institutions